Leadership in Asia challenges and opportunities - Ulrich, David (McGraw Hill, 2010)
The Asian economy continues to grow rapidly. As such, it is imperative that Asian organizations build leadership depth if they are to capture and sustain this growth. For leaders do matter: they help employees stay committed, customers receive products, communities stay respectful and investors remain confident. Recognizing the need to discuss issues related to building the next generation of leaders in Asia, the Singapore Ministry of Manpower hosted an Executive Roundtable in May 2009. The forum involved leading executives and thought leaders from across a wide range of industries and sectors. The topics debated ranged from developing talent management philosophies and strategies for Asia and tailoring global leadership development practices for leaders in the region, to implementing programmes for attracting, grooming and retaining future CEOs and tackling present and future challenges related to meeting leadership demands in the region.